2017
DOI: 10.1590/0074-02760160412
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of four molecular approaches to identify Candida parapsilosis complex species

Abstract: Since the description of Candida orthopsilosis and C. metapsilosis in 2005, several methods have been proposed to identify and differentiate these species from C. parapsilosis sensu stricto. Species-specific uniplex polymerase chain reaction (PCR) was performed and compared with sequencing of the D1/D2 region of the LSU 28S rDNA gene, microsatellite typing of C. parapsilosis sensu stricto, and PCR-restriction fragment length polymorphism patterns in the ITS1-5.8S-ITS2 region of the rDNA gene. There was agreeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
(44 reference statements)
0
4
0
1
Order By: Relevance
“…Hass et al applied the matrix assisted laser desorption ionization-time of flight mass spectrometry method for the discrimination of these species (20). Moreover, Barbedo et al reported agreement in the results of four PCR-based methods (i.e., species-specific uniplex PCR, sequencing of the D1/D2 region of the LSU 28S rDNA gene, microsatellite typing, and PCR-RFLP of ITS) for species identification among 98 clinical isolates (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hass et al applied the matrix assisted laser desorption ionization-time of flight mass spectrometry method for the discrimination of these species (20). Moreover, Barbedo et al reported agreement in the results of four PCR-based methods (i.e., species-specific uniplex PCR, sequencing of the D1/D2 region of the LSU 28S rDNA gene, microsatellite typing, and PCR-RFLP of ITS) for species identification among 98 clinical isolates (5).…”
Section: Discussionmentioning
confidence: 99%
“…It is considered as a nosocomial yeast pathogen that causes a high variety of clinical manifestations such as endocarditis, fungemia, septic arthritis, pancreatitis, endophthalmitis, and meningitis (2). Since the early 1990s, based on a variety of molecular studies such as randomly amplified polymorphic DNA analysis (RAPD) (3), mitochondrial DNA sequences analysis (4), and internal transcribed spacer (ITS) sequencing (5), C. parapsilosis has been categorized as a complex consisting of three genetically distinct groups (named I, II and III). Tavanti et al replaced the groups II and III with C. orthopsilosis and C.metapsilosis based on multilocus sequence typing (MLST) data and identified three separate species as the C. parapsilosis complex (6).…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of the detection molecular methods depends on various factors, one of the most important of which is the selection of the target DNA for amplification. Over the last two decades, the use of molecular diagnostic study for the detection of a specific sequence of Candida to investigate intra-species and inter-species differences has been reviewed [18,19]. In such studies, when the main purpose was to design pan-Candida primers, the designed primer pair usually amplified common environmental contaminants, such as Aspergillus.…”
Section: Discussionmentioning
confidence: 99%
“…The internal transcription spacer (ITS) of the rDNA locus has been acknowledged as the worldwide gold standard for fungal species identification [24,25], and various global primers amplify this region. Other parts of the rDNA locus, such as Trichosporum's Intergenic Spacer region 1 (IGS1) may be more useful for identifying certain clusters or species [26].…”
Section: End-point Pcr-based Amplificationmentioning
confidence: 99%